2011
DOI: 10.1590/s1516-14392011005000067
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis and electronic structure of chiral carbon and carbon nitride nanotubes

Abstract: Geometry and electronic structure of chiral carbon and carbon nitride (CNx) nanotubes were investigated through quantum chemical methods. Finite nanotubes with diameters ranging from 5 to 10 Å and containing up to 500 atoms were considered. CNx structures were built through random substitution of carbon atoms by nitrogen. The molecules were fully optimized by semi-empirical quantum chemical method (PM3). Our results show that the energy associated with nitrogen incorporation depends strongly upon the tube heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Depending on the ratio between chirality indexes, they display features of conductors or semiconductors [252] and have valuable optical properties [253]. It was shown that the doping of chiral nanotubes with nitrogen diminishes the stress caused by the small diameter and the corresponding energy strongly depends on the tube helicity [254]. However, the most prominent quality of chiral nanotubes is their ability to form complexes with chiral molecules possessing different degrees of stability.…”
Section: Recognition Of the R-and S-isomers By Chiral Nanotubesmentioning
confidence: 99%
“…Depending on the ratio between chirality indexes, they display features of conductors or semiconductors [252] and have valuable optical properties [253]. It was shown that the doping of chiral nanotubes with nitrogen diminishes the stress caused by the small diameter and the corresponding energy strongly depends on the tube helicity [254]. However, the most prominent quality of chiral nanotubes is their ability to form complexes with chiral molecules possessing different degrees of stability.…”
Section: Recognition Of the R-and S-isomers By Chiral Nanotubesmentioning
confidence: 99%
“…The geometry optimization criteria GNORM was set at 0.001 for the isolated molecules by PM3 methods (de Faria et al 2011). A total of 11 MOPAC derived descriptors reflecting the most character of the molecules were selected and calculated in this study.…”
Section: Methodsmentioning
confidence: 99%